PENGARUH PELAKSANAAN PENGAWASAN TERHADAP KINERJA KARYAWAN RITEL MODERN (KASUS KARYAWAN FRONTLINER PT. METRO ABADI SEMPURNA SEMESTA - ", Surani; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Supervision is series activity that be done consciously and systematicy by manager to ascertain that all operational action be run truly according to plan that had to be made previous. Supervision can be done in form direct also undirect by Manager or people who be gave authority by company.Performance is level succeedness someone according to entirely as long as one surest periods inside to execute it task to be compared with various possibility, like work result standart, target or criteria. As indicator of working performance individualy is: working quality, pressal quality, quantity, correctness time, effectivity, and stand aloneness.In ritel's business, frontliner's employee has role that very big that is as company spear end. Frontliner’s task working is interact directly to consumer, must able to give it a optimal service so that consumer can feel satisfy. Existence the supervision that be done will make employee to work according to what was have been decided by company and ascertain that the job be done to goodly.This research Result show that the influency supervision execution in working performance. It can be seen from result be knowing t count (6,833) >; table (3,120) and Sig (0,000) < 0,05. So hypothesiical that to state it that existence supervision execution influence in performance can be accepted.key word : Influence, Supervision, Performance.